자기조절학습 전략 중심 수업이 L2 학습자의영어 독해능력에 미치는 영향 - 주용균; 맹은경 (언어과학연구, 2018)
The purpose of this study is to investigate the effect of self-regulated learning strategy instruction (SRLI) on L2 learners' reading comprehension. Fifty high school students participated in this study, and 30 reading test items were selected from past tests and used to measure their reading comprehension. Independent sample t-tests and paired t-tests were used to analyze the data. Overall, the results of this study show that SRLI is very effective in enhancing students’ reading comprehension. The experiment group exposed to SRLI experienced more positive attitudes and perceptions than the control group. More specifically, the autonomy, metacognition, efficiency, motivation, and self-efficacy of experimental group students were improved through SRLI.
Keywords: self-regulated language learning; reading ability; metacognition; (motivation; self-efficacy; 자기조절학습; 독해능력; 메타인지; 학습동기; 자기효능감